ALTERNATIF KEBIJAKAN PERATURAN DAERAH PERSPEKTIF GENDER BAGI BURUH MIGRAN PEREMPUAN DI MADURA - Rahayu, Devi ([Yogyakarta] : Universitas Gadjah Mada, 2012)
Problemsfaced by Women Migrant Worker partly incurred in connection with the position of their woman role that have occurred since the time of recruitment process until departure and when returning back to their home areas. The presence of a legal loophole in the Law 39 of 2004 is one of the problems. The existence of a gender perspective of regional policy is an effort to guarantee the rights of migrant workers and as a solution to problems related to the position of migrant workers.